2006
DOI: 10.1111/j.1365-2934.2006.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision: what do we know and what do we need to know? A review and commentary

Abstract: Nursing knowledge concerning many aspects of clinical supervision is increasing because of research. Much of the literature suggests that clinical supervision is scholarly activity requiring much the same attention to relationships as the therapeutic activities it supports. This discussion concludes with the idea that clinical supervision might work at its best as a quiet activity allowing nurses to think about nursing work in ways that suit individual learning styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 60 publications
0
33
0
1
Order By: Relevance
“…According to Jones (2006), supervision of this kind can generate both anxiety and stress. On the contrary, in the present study, the group stresses the importance of the group supervision sessions for discussing professional situations and difficult issues in a spirit of trust and collegiality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Jones (2006), supervision of this kind can generate both anxiety and stress. On the contrary, in the present study, the group stresses the importance of the group supervision sessions for discussing professional situations and difficult issues in a spirit of trust and collegiality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies revealed positive effects of supervision, as it could reduce occupational stress (Williamsson and Dodds, 1999). The process is further described as cost effective, supportive and safe (Jones, 2006;Scott and Smith, 2008;Walsh et al, 2003;Lindgren et al, 2005). According to Jones (2006), group supervision also creates conditions for a group of colleagues to enhance their professional learning and improve their efforts.…”
Section: Collegial Group Supervisionmentioning
confidence: 90%
See 3 more Smart Citations